THE EFFECT OF TEAM ORIENTATION, CREATING CHANGE AND CUSTOMER FOCUS ON INNOVATION AND EMPLOYEE PERFORMANCE ON PT. PELINDO III (PERSERO) BANJARMASIN - Muhammad Rendy Faisal (Jurnal Apresiasi Ekonomi, 2019)
This research aims to analyze the influence of Team Orientation, Creating Change and Customer Focus on Innovation and Employee Performance at PT Pelabuhan Indonesia III Banjarmasin. The sampling method used proportional stratified random sampling, which sample was as many as 145 people. The research data used a questionnaires which were distributed online using links that can be clicked from e-mail and also social media whatsapp with smartphones and laptops / PCs. Structural Equation Modeling (SEM) is a method of data analysis used in this research. The results of this research indicated that Team Orientation affects Innovation, Creating Change affects Innovation, Customer Focus affects Innovation, Team Orientation affects Employee Performance, Creating Change affects Employee Performance, Customer Focus has no effect on Employee Performance and Innovation affects Employee Performance. Keywords :Team Orientation, Creating Change, Customer Focus, Innovation, Employee Performance